The Effect of Good Corporate Governance, Sales Growth, and Capital Intensity on Accounting Conservatism (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2017-2019) - Achyani, Fatchan; Lovita, L; Putri, Eskasari (Universitas Muhammadiyah Surakarta, 2021)
The company’s condition must experience ups and downs that cause instability so that conditions are different from one company to another. Companies must be meticulous in financial reporting to attract investors and creditors as users of financial information. Companies do not rush to recognize and measure assets and profits and immediately recognize possible losses and debts. The purpose of this study is to analyze and obtain empirical evidence about the effect of good corporate governance, sales growth, and capital intensity on accounting conservatism. In this study, indicators of good corporate governance are managerial ownership, independent commissioners, audit quality, and concentrated ownership. The sample of this research was manufacturing companies in Indonesia during 2017-2019, which are listed on the Indonesia Stock Exchange (BEI). This study results indicated that independent commissioners and capital intensity influenced accounting conservatism.